2010
DOI: 10.1093/jac/dkq301
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue-mediated photodynamic inactivation as a novel disinfectant of enterovirus 71

Abstract: Methylene blue-mediated photodynamic inactivation may provide a novel way to eliminate environmentally contaminated sources of EV71 to prevent infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…In fact, although it has been shown that both enveloped and nonenveloped viruses can be efficiently inactivated due to the damages induced by photodynamic procedure on viral proteins Malik et al, 1993;Moor et al, 1997;Smetana et al, 1998;Hotze et al, 2009;Wong et al, 2010), there is still scarce information about the type of damage induced to phage proteins and which are the most affected proteins. For this reason, it is important to pursue in the development of novel, convenient and fast-preparation methods to evaluate and characterize the damages induced by photosensitization on viral molecular structures.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, although it has been shown that both enveloped and nonenveloped viruses can be efficiently inactivated due to the damages induced by photodynamic procedure on viral proteins Malik et al, 1993;Moor et al, 1997;Smetana et al, 1998;Hotze et al, 2009;Wong et al, 2010), there is still scarce information about the type of damage induced to phage proteins and which are the most affected proteins. For this reason, it is important to pursue in the development of novel, convenient and fast-preparation methods to evaluate and characterize the damages induced by photosensitization on viral molecular structures.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the same treatment is reported to be ineffective against some non-enveloped viruses [83,131], the results from Wong et al [85] showed that even a non-enveloped virus can be efficiently inactivated due to the damage induced by PDI to its viral proteins (Table 4). …”
Section: Molecular Targets Of Antiviral Pdimentioning
confidence: 99%
“…The protein profile of the non-enveloped enterovirus 71 was considerably altered after a low dose PDI and a MB concentration ≥0.5 μM, as revealed by a smearing and the disappearance of several protein bands [85]. However, enterovirus 71 PDI was also due to damages in the viral genome [85].…”
Section: Molecular Targets Of Antiviral Pdimentioning
confidence: 99%
“…Our related study showed that whole body exposures to EV71 viral suspension are an effective and less stressful alternative for inducing the lethal infection of newborn mice via the oral route [75]. In laboratory mice, fecal-oral transmission of EV71 between infected and non-infected littermates occurs after close contact [6,15].…”
Section: Reviewmentioning
confidence: 99%